Tracheal agenesis, a frightening scenario. Issue 3 (7th January 2016) - Mohammed, H; West, K; Bewick, J; Wickstead, M
Abstract: Objective: This paper discusses three cases of tracheal agenesis that presented within a six-week period to the Norfolk and Norwich University Hospital. By reviewing the available literature on tracheal agenesis, the report aims to outline a protocol for future prenatal and postnatal management. Methods: A case series and a literature review. Results: Three cases of tracheal agenesis presented in the classical manner, with respiratory distress and unsuccessful intubation following delivery. A literature review confirmed that prenatal diagnosis requires future innovation; survival is rare and is predominately reliant on intubation of the oesophagus when a patent tracheoesophageal fistula is present. In most cases, tracheal agenesis represents part of the 'VATER' association: vertebral defects, anal atresia, tracheoesophageal fistula with oesophageal atresia, and radial or renal dysplasia. Complex, multiple-stage surgical procedures have been described; however, no survival to adolescence is documented. Conclusion: There is a call for improved prenatal diagnosis to allow both adequate counselling of parents and preparation for multi-specialty management at delivery. In addition, these cases highlight the ongoing need for improved congenital anomaly data within the UK, with currently only 49 per cent of England's births being registered.